The digital coexistence and its problems: a study with adolescents from São Paulo state public schools - Farhat, Fernanda Issa de Barros[UNESP]; Goncalves, Catarina Carneiro (Unesp-faculdade Ciencias & Letras, 2022)
The forms of coexistence are crossed by multiple variables, so that the current technological apparatuses not only mark the interactions between people but also build different forms of relationships in contemporaneity. In this way, physical and virtual environments merge, configuring possibilities of real coexistence that impact on relationships between people, especially in pandemic times in which interpersonal relationships mediated by virtual platforms have been greatly enhanced. Recognizing this reality, it is urgent to reflect on: How does the coexistence between adolescents occur in virtual environments? What are the biggest difficulties of coexistence that does not include physical contact? Aiming to reflect on these questions, a descriptive study was conducted on cyber coexistence/cyber aggression seeking to identify how how the behaviors and interactions occurring in virtual environments are characterized. The instrument for data collection was a structured questionnaire, containing 15 questions about the theme, applied virtually through a form via Google Forms. The participants of the study comprised a sample of 1,923 adolescents, students from two directorates of the Sao Paulo state public school system: the DRE Leste 3 in the metropolitan region of Sao Paulo with 1,056 respondents and the DRE of Taquaritinga, in the countryside of Sao Paulo, with 867 adolescents. We found a sample of almost 40% of students responding that they had already been insulted in virtual interactions, experiencing pain and suffering in this form of coexistence.
Keywords: Virtual interaction; Coexistence; Empathy; Pandemic; Internet